Avaliação da utilização das cinzas da escuma gerada em Reator Anaeróbico de Manta de Lodo e Fluxo Ascendente como pigmento inorgânico de coloração alaranjada - Fiuza, Tanna Elyn Rodrigues; de Souza, Eder Carlos Ferreira [UNESP]; Antunes, Sandra Regina Masetto; Costa, Wilson [UNESP]; Arrúa, Maria Elena Payret; Antunes, Augusto Celso (FapUNIFESP (SciELO), 2017)
Scum is a residue generated during the anaerobic treatment of domestic effluents and requires periodical removal in order not to harm the process efficacy. This study aimed to use the scum ashes generated from Upflow Anaerobic Sludge Blanket (UASB) reactor as inorganic pigments. The scum samples collected in different months were thermally treated at 900°C for one hour for removal of organic matter. These ashes were dispersed and submitted to chemical (X-ray Fluorescence – XRF), mineralogical (X-ray Diffraction – XRD), morphological (Field Emission Scanning Electron Microscopy – FE-SEM) and color (Ultraviolet-Visible Diffuse Reflectance Spectroscopy – UV-Vis DRS) analyses. The samples were composed mainly by elements commonly found in the environment. The main crystalline phases are quartz (silicon dioxide – SiO2), anhydrite (calcium sulfate – CaSO4) and hematite (iron oxide – Fe2O3). Also, these particles presented suitable size for application as ceramic pigment and the color obtained was intense orange. When applied as ceramic pigment at the decorative fire temperature, the enameled piece presented intense color and the pigment had good opacity, hiding the ceramic support color, besides, they presented no surface deformations, which indicates the pigments are compatible with enamel. Thus, scum ashes generated in UASB reactor presented interesting characteristics to be applied as ceramic pigments.
Evaluation of the use of ashes of scum generated from the upflow anaerobic sludge blanket reactor as orange inorganic pigment
Keywords: Inorganic pigment; Residue; Scum; Sewage